Nutritional evaluation of canola meals produced from new varieties of canola seeds for poultry. (17th March 2015) - Chen, X.; Parr, C.; Utterback, P.; Parsons, C. M.
Abstract : This study evaluated the nutritional value of 14 canola meals from new varieties of canola and compared them to conventional canola meal samples and soybean meals in chickens. Five experiments that included different sources of canola meals or soybean meals were conducted. For each experiment, a precision-fed rooster assay with conventional or cecectomized roosters was conducted to determine TMEn or amino acid digestibility. Analyzed nutritional composition of the canola meal samples indicated increases in crude protein and amino acids for all test canola meals (49.41 to 50.58% crude protein on a dry matter basis) compared to conventional canola meals (40.73 to 43.01%). All test canola meals also contained lower amounts of neutral detergent fiber and acid detergent fiber. Most test canola meals had significantly higher TMEn values than the conventional canola meals ( P < 0.05), but all were lower than the soybean meal ( P < 0.05). The test canola meals had higher amino acid digestibility coefficients than conventional canola meals in Experiments 1, 2, and 4 ( P < 0.05), and higher concentrations of digestible amino acids in all 5 experiments. The results of this study indicated that nutritional value of the canola meal from new varieties of canola was greater than conventional canola meal for poultry.